HUBUNGAN ANTARA GAYA BELAJAR VISUAL DENGAN HASIL BELAJAR SISWA KELAS XI MADRASAH ALIYAH - Khadafi, Muammar; Diana, Elys Surya; Mujiburrahman, Mujiburrahman; Sarilah, Sarilah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Learning outcomes represent the level of ability achieved by a person after undergoing the learning process. Many factors influence students' learning outcomes, one of which is learning style. A lack of understanding of their own learning styles may prevent students from optimally absorbing, understanding, and achieving the expected learning outcomes. Therefore, this study aims to determine the relationship between visual learning style and the learning outcomes of eleventh grade students at MAN 1 West Lombok. This study employed a quantitative approach with a correlational design. The population of this study consisted of all eleventh grade students of MAN 1 West Lombok in the 2023/2024 academic year, totaling 178 students. The sample consisted of 30 students selected using the simple random sampling technique. The data collection methods used in this study were questionnaires and documentation as supporting data. The data analysis technique used was the Pearson Product Moment correlation test. Based on the results of the correlation test, the correlation coefficient (r) between visual learning style and students' learning outcomes at the 5% significance level was 0.153. This value falls within the correlation interpretation index range of 0.00–0.20, which is categorized as very low. Thus, the calculated r value is smaller than the r table value (0.153 < 0.50), indicating that Ha is rejected and Ho is accepted. Therefore, the results of this study indicate that the relationship between visual learning style and students' learning outcomes is not significant. ABSTRAK Hasil belajar merupakan tingkat kemampuan yang diperoleh seseorang setelah melalui proses belajar. Banyak faktor yang mempengaruhi hasil belajar siswa, salah satunya adalah faktor dari gaya belajar yang milikinya. Kurangnya pemahaman terhadap gaya belajar yang dimilikinya, menjadikan siswa kurang maksimal dalam menyerap, memahami dan memperoleh hasil belajar yang diinginkannya. Maka dari itu penelitian ini bertujuan untuk mengetahui hubungan antara gaya belajar visual dengan hasil belajar siswa kelas XI MAN 1 Lombok Barat. Penelitian ini merupakan penelitian kuantitatif dengan desain korelasi. Populasi pada penelitian ini yaitu seluruh siswa kelas XI MAN 1 Lombok Barat Tahun Pelajaran 2023/2024 yang berjumlah 178 siswa, dan sampel yang digunakan sejumlah 30 siswa dengan menggunakan perhitungan simple random sampling. Metode pengumpulan data yang digunakan dalam penelitian ini adalah metode angket dan metode dokumentasi sebagai data pendukung. Untuk teknik analisis data, penelitian ini menggunakan uji korelasi “product moment”. Berdasarkan hasil uji korelasi gaya belajar visual dengan hasil belajar siswa menggunakan rumus uji r dengan taraf signifikansi sebesar 5% adalah 0,153 dimana nilai tersebut berada pada rentang indeks interpretasi korelasi yaitu 0,00-0,20 dengan kategori sangat rendah. Dengan demikian nilai r hitung lebih kecil dari nilai r tabel (0,153 < 0,50), maka Ha ditolak dan Ho diterima sehingga hasil penelitian ini dinyatakan tidak signifikan.